2020
DOI: 10.3390/ma13245824
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Condition of Ni-Cr after SiC Abrasive Blasting for Applications in Ceramic Restorations

Abstract: Abrasive blasting is a process widely used in dentistry. One of the uses is the development of metal surfaces for connections with ceramics in fixed prosthetic restorations. The purpose of this paper was to check how the rough surface profile (width, height, and depth on unevenness) impacts the surface’s condition, like its wettability and percentage of stuck abrasives. The Ni-Cr alloy surface was abrasive blasted by silicon carbide with the various pressure parameters (0.2, 0.4, and 0.6 MPa) and abrasive part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The highest strength values were obtained for the abrasive group blasted with 50 µm grain size at a pressure of 400 kPa. This is a new observation concerning research work on an Al 2 O 3 abrasive [ 4 , 5 , 10 , 24 ]. Pietnicki et al report that the optimum shear strength of the Co-Cr alloy and dental ceramics joint is provided after pre-treatment with an Al 2 O 3 abrasive with a 110 µm grit size at a pressure of 400 kPa [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest strength values were obtained for the abrasive group blasted with 50 µm grain size at a pressure of 400 kPa. This is a new observation concerning research work on an Al 2 O 3 abrasive [ 4 , 5 , 10 , 24 ]. Pietnicki et al report that the optimum shear strength of the Co-Cr alloy and dental ceramics joint is provided after pre-treatment with an Al 2 O 3 abrasive with a 110 µm grit size at a pressure of 400 kPa [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that the parameters used in abrasive blasting have different effects on the surface of metals used in prosthetics and on the strength of the metal-ceramic joint [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. For titanium and cobalt-chromium alloys, the parameters that provide the best bond strength values include 110 µm aluminium oxide and a treatment pressure of 400 kPa [ 4 , 5 ], which contradicts the hypothesis that the higher the abrasive blasting parameters, the better the bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Size of abrasive particles and parameters used during sandblasting define the quality of the whole process. [9] Similar thing happens with structural ceramics which have tendency to replace metallic dental prostheses. Kim and Ahn researched influence of particle size of sandblasting abrasives on surface roughness of zirconia.…”
Section: Introductionmentioning
confidence: 88%
“…Numerous studies have indicated that parameters used in abrasive blasting differently affect the surface of metals used in prosthetics and the strength of the metal–ceramic joint [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. According to Gołębiowski and Pietnicki, treatment with 110 μm aluminum oxide under a pressure of 400 kPa provides the best bond strength values for titanium and cobalt–chromium alloys [ 8 , 9 ], which contradicts the hypothesis that the higher the abrasive blasting parameters, the better the bond strength [ 13 ].…”
Section: Introductionmentioning
confidence: 99%